1998
DOI: 10.1103/physrevb.58.4066
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron-radiation photoemission study of Ba on aSi(001)2×1surface

Abstract: A synchrotron-radiation photoemission study of Ba deposited on a clean Si(001)2ϫ1 surface at room temperature is presented. Upon Ba adsorption, the maximum drop in work function is about 2.3 eV. At submonolayer coverage, the asymmetric dimers on the surface are preserved. Near to one monolayer, however, they become symmetric. In the meantime, barium silicides start to form, first the monosilicide followed by the disilicide with increasing coverage. The Si 2p core-level photoemission spectra clearly exhibit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 27 publications
4
13
0
Order By: Relevance
“…This confirms and explains the core-level shift experimental results of Cheng et al, 3 who find a small or zero charge transfer at low coverage, in contrast with the ionic character of the metal silicides obtained at higher coverage ͑above 1 monolayer͒. This result is also consistent with the STM experiments, 8 which indicate only a partial charge transfer from Ba to the surface, as shown in our calculations.…”
supporting
confidence: 93%
“…This confirms and explains the core-level shift experimental results of Cheng et al, 3 who find a small or zero charge transfer at low coverage, in contrast with the ionic character of the metal silicides obtained at higher coverage ͑above 1 monolayer͒. This result is also consistent with the STM experiments, 8 which indicate only a partial charge transfer from Ba to the surface, as shown in our calculations.…”
supporting
confidence: 93%
“…The bonding was shown to be strongly covalent, in contrast to what would be expected from the large electronegativity difference between Si and Ba. Only a small charge transfer of 0.15e was obtained, which explains the core level shifts experimental results of Cheng et al [75] The problem of the diffusion of Ba on the Si(001) surface was also addressed in view of the energetics results obtained in this work. It was found that diffusion is much more likely (seven orders of magnitude) to occur in the direction of the dimer rows than perpendicular to it.…”
Section: Absorption and Growth Of Ba On Si(001)supporting
confidence: 62%
“…The origin of these minor features was discussed earlier. 37,38 Since their introducing did not affect on the other fitting parameters practically, we do not consider the loss features hereafter.…”
Section: Si 2p Core Levelmentioning
confidence: 99%